Identification and Expression Analysis of the CsMYB Gene Family in Root Knot Nematode-Resistant and Susceptible Cucumbers - Cheng, Chunyan; Li, Qingrong; Wang, Xing; Li, Ying; Qian, Chuntao; Li, Ji; Lou, Qunfeng; Jahn, Molly; Chen, Jinfeng (Frontiers in Genetics, 2020)
MYB transcription factors play important roles in controlling various physiological processes in plants, such as responses to biotic and abiotic stress, metabolism, defense etc. Our previous study demonstrated that MYB transcription factor(s) may regulate the major gene, LTP (Csa6G410090), in cucumber (Cucumis sativus L.) for resistance to root-knot nematode (RKN) [Meloidogyne incognita Kofoid and White (Chitwood)], however, the regulation mechanism remained unclear. In this study, by combining CDD and SMART databases, 112 genes were identified as candidate members of the CsMYB gene family. Using the Hidden Markov Model and manual calibration, ten phylogenetic subgroups were resolved. This sequence-based classification was consistent with results from comprehensive investigation of gene structure, conserved motifs, chromosome locations, and cis-element analysis. Amplification of the CsMYB gene family in cucumber mainly relied on tandem repeat events. Spatial gene expression analysis showed that 8 CsMYB genes were highly expressed at differing levels in ten different tissues or organs. The roots of RKN-resistant and susceptible cucumbers were inoculated with M. incognita, finding that CsMYB (Csa6G538700, Csa1G021940 and Csa5G641610) genes might positively respond to the hub gene LTP (Csa6G410090) against RKN in cucumber. Our systematic analysis of the CsMYB gene family further illuminates interactions between CsMYB genes and the major gene, LTP, for resistance to the root knot nematode (RKN), suggesting testable mechanistic hypotheses for resistance and possible strategies to improve levels of resistance to the RKN in cucumber.